Curriculam change: construction of a new pedagogical training project in the field of Speech Therapy - Maria Cecília Bonini Trenche; Luisa Barzaghi; Altair Cadrobbi Pupo; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
The first year of implementation of the new pedagogical project for the Speech Therapy course at the Catholic University of São Paulo (PUC-SP) is analyzed. The aim was not only to analyze the changes in pedagogical concepts and practices, but also to construct collective work by the social body of the course. The results indicated that the new pedagogical activities (seminars, tutorials, workshops and instructive experiences) were important tools for achieving the proposed changes in the new curricular model. Highlighted among other advances were: greater integration between basic disciplines and professionalizing activities; better comprehension by students of the importance of training based on the population's needs; greater linkage between teaching, research and extension activities; interaction among students at various levels of training, regarding health promotion and disease prevention actions; planning of supplementary pedagogical activities according to students' needs detected in educational assessments.